Let parliament be one of reconciliation - Abd Razak, Dzulkifli (2008)
DEMOCRACY in this country is very much alive and kicking. Although many used to have cynical views about it —it was often a case of sour grapes—this may not be so after the recent general election. Most were stunned by the "tsunamilike" sociopolitical impact which numbed almost everyone, not unlike that of the Aceh tragedy of 2004. There is, however, one important difference: everything is still intact, all is not lost. The political shift is perhaps best epitomised by the image of the ballot boxes itself. From an "opaque usedtin biscuit box" way back then, it has been transformed into a sophisticated, tailormade transparent box befitting the 21st century. Not only are the differences in physical appearance so stark, even more so, metaphorically speaking.